Determinants of Contraceptive Use and Fertility in Buleleng District - Made Indriyani Puspita Sari; Anak Agung Istri Ngurah Marhaeni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Fertility is one of the key indicators in population dynamics, influenced by various factors. This study aims to analyze: 1) public perception of the knowledge, attitude, and practice (KAP) of Krama Bali family planning (KB); 2) the influence of education, employment status, and KAP of Krama Bali family planning on contraceptive use; 3) the influence of education, employment status, KAP of Krama Bali family planning, and contraceptive use on fertility; and 4) the role of contraceptive use in mediating the influence of education, employment status, and KAP of Krama Bali family planning on fertility. This research employs a quantitative approach with an associative design. The sample consists of 99 individuals, specifically married couples of reproductive age (40–45 years) in Buleleng District. The sampling techniques used include accidental sampling, snowball sampling, and purposive sampling. Data collection methods include observation, interviews, and in-depth interviews. The data analysis involves descriptive statistics, path analysis, and the Sobel test. The study results indicate: 1) Public perception of Krama Bali family planning is mostly positive, with most respondents understanding and accepting it. However, the practice of having four children, as recommended by Krama Bali family planning, is less common due to the risks of late-age pregnancy. 2) Education has a significant positive effect on contraceptive use, with employed respondents using contraceptives for a longer duration than unemployed respondents. Meanwhile, the KAP of Krama Bali family planning has a significant negative effect on contraceptive use. 3) Education and contraceptive use have a significant negative effect on fertility, with employed respondents having lower fertility than unemployed respondents. In contrast, the KAP of Krama Bali family planning has a significant positive effect on fertility. 4) Contraceptive use partially mediates the effects of education, employment status, and the KAP of Krama Bali family planning on fertility.